Traveling Wave Solutions of the Benjamin-Bona-Mahony Water Wave Equations. (15th October 2014) - Seadawy, A. R.; Sayed, A.
Abstract : The modeling of unidirectional propagation of long water waves in dispersive media is presented. The Korteweg-de Vries (KdV) and Benjamin-Bona-Mahony (BBM) equations are derived from water waves models. New traveling solutions of the KdV and BBM equations are obtained by implementing the extended direct algebraic and extended sech-tanh methods. The stability of the obtained traveling solutions is analyzed and discussed.